2018
DOI: 10.18632/oncotarget.24150
|View full text |Cite
|
Sign up to set email alerts
|

A metabolomic study on early detection of steroid-induced avascular necrosis of the femoral head

Abstract: The early and accurate diagnosis of steroid-induced avascular necrosis of the femoral head (SANFH) is appealing considering its irreversible progression and serious consequence for the patients. The purpose of this study was to investigate the metabolic change of SANFH for its early detection. Two stages were designed in this study, namely discovery and verification. Except the biochemical index anomaly and the accidental death, 30 adult healthy adult Japanese white rabbits were used for screening out the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…According to the related reference [35], the samples were taken at the speci c nodes and serum samples were prepared. Above 3 mL venous blood was gotten from speci c rabbits.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the related reference [35], the samples were taken at the speci c nodes and serum samples were prepared. Above 3 mL venous blood was gotten from speci c rabbits.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…The indexes were as follows: 3D T 2 WI VISTA (TR 2600 ms, TE 200 ms), slice thickness 1.2 mm, ip angle 90 deg and matrix (reconstruction 256 × matrix scan 256). Then the MRI results of lovastatin for treatment of SANFH were researched [35].…”
Section: Magnetic Resonance Imaging Scanmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pathogenesis of steroid-induced ONFH is still not very clear. Presently, osteoblast apoptosis, 10,11 lipid metabolism abnormality, 12 intravascular coagulation, 13 and vascular endothelial dysfunction 14 are hypothesized as factors causing ONFH. However, a study indicated that the pathogenesis of steroid-induced ONFH was the result of a comprehensive effect of multiple factors.…”
Section: Introductionmentioning
confidence: 99%
“…Avascular necrosis is an adverse outcome of femoral neck fractures, and adequate reduction and internal fixation may reduce avascular necrosis after osteosynthesis. The femoral head avascular necrosis rate in the elderly can be decreased through closed reduction and fixation, and reduction quality, fracture type, and the timing of the operation are closely correlated with femoral head avascular necrosis. Several studies have explored the risk differences of avascular necrosis in femoral neck fractures in children and adolescents who have received open reduction or closed reduction.…”
Section: Introductionmentioning
confidence: 99%